2006
DOI: 10.1097/00001163-200610000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Social-Emotional Development of Infants and Young Children With Orofacial Clefts

Abstract: Children with orofacial clefts are believed to have distinctly elevated risk for a variety of adverse social-emotional outcomes including behavior problems, poor self-concept, and parent-child relationship difficulties. This assumption has been based primarily on theories of facial appearance and social bias, a handful of empirical studies, and clinical impressions. Studies of these children have been limited by methodological problems such as diagnostic heterogeneity, ascertainment bias, and absent or poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 72 publications
2
26
0
2
Order By: Relevance
“…(Young et al, 2001). From a cultural perspective, we did find that parents have a superstition problem in Taiwan; there is support for this in the literature (Collett and Speltz, 2006;Olasoji et al, 2007). One of the items in the SSPCC, S29, which emerged from phase 1, is ''the cause of the condition is misunderstood as a result of superstitions,'' and in response to this, one of the participants mentioned that ''someone said that if you have done something wicked in your previous life or invaded the God of fetus during pregnancy, and you will give birth to a child with CL/P.''…”
Section: Discussionsupporting
confidence: 53%
“…(Young et al, 2001). From a cultural perspective, we did find that parents have a superstition problem in Taiwan; there is support for this in the literature (Collett and Speltz, 2006;Olasoji et al, 2007). One of the items in the SSPCC, S29, which emerged from phase 1, is ''the cause of the condition is misunderstood as a result of superstitions,'' and in response to this, one of the participants mentioned that ''someone said that if you have done something wicked in your previous life or invaded the God of fetus during pregnancy, and you will give birth to a child with CL/P.''…”
Section: Discussionsupporting
confidence: 53%
“…Self‐concept and its associated outcomes in youth with craniofacial differences, especially cleft lip and palate, have been examined extensively, although results have been inconsistent. In their 2006 review, Collett and Speltz (23) found that a handful of studies supported the long‐believed notion that children with clefts had lower ratings of self‐worth (24–26); but, this finding has not been consistent across studies or across subdomains of self‐concept. Others have found that those children with clefts have average (27–29) to above‐average (30) self‐concept when compared with youth without clefts.…”
Section: Self‐concept and Physical Appearancementioning
confidence: 99%
“…Environmental factors also may place children with clefts at risk. The quality of mother-child interactions has been the focus of several investigations (see review by Collett and Speltz, 2006). Findings from these studies have been inconsistent; however, there is some indication that the mothers of preschoolers with clefts are more directive than the mothers of unaffected controls, particularly during teaching interactions (e.g., Allen et al, 1990; Wasserman and Allen, 1985).…”
mentioning
confidence: 99%